How do you evaluate 2x^2 - 2z^4 + y^2 - x^2 + z^4 if x = -4, y = 3, and z = 2?
1 Answer
Jun 30, 2016
Explanation:
Given,
2x^2-2z^4+y^2-x^2+z^4
Knowing that
=2(-4)^2-2(2)^4+(3)^2-(-4)^2+(2)^4
Recall that a number raised to a power
=2(color(red)(-4)*color(red)(-4))-2(color(blue)2*color(blue)2*color(blue)2*color(blue)2)+(color(darkorange)3*color(darkorange)3)-(color(purple)(-4)*color(purple)(-4))+(color(teal)2*color(teal)2*color(teal)2*color(teal)2)
Simplify.
=2(color(red)16)-2(color(blue)16)+(color(darkorange)9)-(color(purple)16)+(color(teal)16)
=32-32+9-16+16
=color(green)(|bar(ul(color(white)(a/a)color(black)9color(white)(a/a)|)))